Comparative Analysis of Rainbow Trout Strains Reared in Aquaculture Systems - Arnautov Maksim V.; Bindyukov Sergej V.; Gershunskaya Valeriya V. (BIO Web of Conferences)
This study examined market-sized rainbow trout (Oncorhynchus mykiss) from European strains with varying traits, including diploid, triploid, and sterile forms. The fish were raised in concrete flow-through tanks at Ostrov-Aquaculture LLC (Republic of North Ossetia-Alania) until reaching a market weight exceeding 2 kg. Key parameters assessed included size, weight, morphometric traits, internal organ indices, and muscle tissue nutrient composition. Results indicated minimal weight differences among most strains, except for trout derived from Norwegian-origin eggs. Fulton’s condition factor was consistent across strains (1.7–1.9), surpassing values typical of domestic breeds. Relative head length remained below 16% and showed no variation with growth. The hepatosomatic index (HSI) ranged from 1.15–1.28% for French and Norwegian strains but was slightly elevated (1.70–1.75%) in Spanish and Danish strains, exceeding the physiological norm (1.5%). French-origin triploid sterile trout exhibited the lowest gonadosomatic index. Muscle tissue analysis revealed no significant differences in protein or fat content across strains, ploidy levels, or gonad development stages. The findings suggest that both diploid and triploid eggs from diverse rainbow trout strains are suitable for commercial farming, achieving target weights over 2 kg within 14–18 months.